Important factors for effective patient safety governance auditing: a questionnaire survey - Saskia C. van Gelderen; Marieke Zegers; Paul B. Robben; Wilma Boeijen; Gert P. Westert; Hub C. Wollersheim (BMC, 2018)
Abstract Background Audits are increasingly used for patient safety governance purposes. However, there is little insight into the factors that hinder or stimulate effective governance based on auditing. The aim of this study is to quantify the factors that influence effective auditing for hospital boards and executives. Methods A questionnaire of 32 factors was developed using influencing factors found in a qualitative study on effective auditing. Factors were divided into four categories. The questionnaire was sent to the board of directors, chief of medical staff, nursing officer, medical department head and director of the quality and safety department of 89 acute care hospitals in the Netherlands. Results We approached 522 people, of whom 211 responded. Of the 32 factors in the questionnaire, 30 factors had an agreement percentage higher than 50%. Important factors per category were 'audit as an improvement tool as well as a control tool', 'department is aware of audit purpose', 'quality of auditors' and 'learning culture at department'. We found 14 factors with a significant difference in agreement between stakeholders of at least 20%. Amongst these were 'medical specialist on the audit team', 'soft signals in the audit report', 'patients as auditors' and 'post-audit support'. Conclusion We found 30 factors for effective auditing, which we synthesised into eight recommendations to optimise audits. Hospitals can use these recommendations as a framework for audits that enable boards to become more in control of patient safety in their hospital.